Assessing effective interventions to improve trial retention: do they contain behaviour change techniques? - Eilidh M. Duncan; Tina Bennett; Katie Gillies (Trials, 2020)
Abstract Background Clinical trials often struggle to retain the number of participants required to make valid and reliable assessments about the effectiveness of treatments. Several individual randomised comparisons of interventions to improve retention in trials have been shown to be effective. Many of these retention interventions target participants’ behaviour (e.g. returning questionnaires or attending a follow-up visit). Although not designed as such, these interventions can be thought of as behaviour change interventions. By coding the constituent behaviour change components of effective retention interventions, the interventions’ potential ‘active ingredients’ responsible for improvements in retention can be identified and maximised for future gains. Methods Studies reporting effective retention interventions were identified from existing meta-analyses in the literature. Published manuscripts and intervention and comparator group material were coded into their behaviour change techniques (BCTs) using the BCT taxonomy version 1. Two authors independently coded materials using a standardised coding manual and discussed any disagreements to reach consensus. Data on study characteristics including host trial context, timing, mode of delivery and dosage of retention intervention were recorded. Results Two intervention types were identified as having evidence of improving retention in existing meta-analyses: monetary incentives and electronic prompts. None of the interventions identified from the included studies explicitly stated a theoretical rationale for their development. BCTs were identified in both intervention and comparator groups across both intervention types and there was heterogeneity with regard to their presentation within and across interventions. The BCTs identified in the ‘monetary incentive’ interventions differed to the comparator group. Contrastingly, the BCTs identified in ‘electronic prompts’ interventions were identical in both the control and intervention groups (within studies) and differed only in terms of mode of delivery and dosing. Conclusions Attending a measurement visit or returning a questionnaire is a behaviour and trialists should be mindful of this when designing retention interventions. Our work in this area provides some of the first evidence of the impact of implicit use of BCTs in retention interventions and highlights their potential promise for future trials.